2016
DOI: 10.1007/s40095-016-0219-z
|View full text |Cite
|
Sign up to set email alerts
|

Preliminary assessment of uranium mining legacy and environmental radioactivity levels in Sabugal region, Portugal

Abstract: An environmental radioactivity survey carried out in the Sabugal region, Portugal, showed enhanced radioactivity levels in surface water streams related to water discharges from old uranium mines. Water from irrigation wells in this region displayed variable radionuclide levels due to natural occurrence of radionuclides and to contamination by mine water drainage. Horticulture products grown near the uranium mine sites contained elevated radium ( 226 Ra) concentrations, but lower concentrations of uranium and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 17 publications
(8 citation statements)
references
References 19 publications
0
7
1
Order By: Relevance
“…The mean specific activity for 226 Ra obtained in this study was about 40 times greater than the WHO reference value of 0.050 Bq/kg and one to two orders of magnitudes higher than the results of similar studies. The mean specific activity of 232 Th from this study was also one to two orders of magnitudes higher than the values reported from similar studies of Choi et al (2008), Harb (2015) and Carvalho, Oliveira, and Malta (2016) and about 56 times greater than the WHO reference values of 0.015 Bq/kg for leafy vegetables. The mean specific activity recorded in this study for 40 K was about 50% lower than the result reported by Choi et al (2008) but about 32% higher than the average results reported by Shanthi et al (2010) and Harb (2015).…”
Section: Resultscontrasting
confidence: 72%
“…The mean specific activity for 226 Ra obtained in this study was about 40 times greater than the WHO reference value of 0.050 Bq/kg and one to two orders of magnitudes higher than the results of similar studies. The mean specific activity of 232 Th from this study was also one to two orders of magnitudes higher than the values reported from similar studies of Choi et al (2008), Harb (2015) and Carvalho, Oliveira, and Malta (2016) and about 56 times greater than the WHO reference values of 0.015 Bq/kg for leafy vegetables. The mean specific activity recorded in this study for 40 K was about 50% lower than the result reported by Choi et al (2008) but about 32% higher than the average results reported by Shanthi et al (2010) and Harb (2015).…”
Section: Resultscontrasting
confidence: 72%
“…Also known as air pollution, it refers to the contamination of the air by gases, liquids and suspended solid particles, biological matter and even energy. The consequences of environmental pollution in Boké are caused by mining [22]. Bauxite dust on crops, water and their health, the populations living along the roads and mining sites of Boké periodically revolt against the authorities whom they accuse of being kind to the mining companies [23].…”
Section: Literature Review Environmental Impact Caused By Mining Exploration (Air Pollution Caused By Mining)mentioning
confidence: 99%
“…Acid mine drainage often results from exposure of rock minerals and ore deposits to water and oxygen facilitating the mobilization of chemical elements and increasing their concentrations in waters and food chains, with detrimental effects on ecosystems’ health and human health (Carvalho et al. , ,b; Hudson‐Edwards et al. ; Nordstrom ).…”
Section: Mining Industry and Legacy Impactsmentioning
confidence: 99%
“…For example, in USA, Germany, France, and Portugal, it was concluded that tailings and acid mine drainage were sources of radioactive contaminants enhancing environmental radioactivity in water, soils, and agriculture products (IAEA, ; Merkel and Arab (); Carvalho et al. , ,b). Environmental remediation projects were implemented and many of these former uranium sites went through clean up and remediation measures which include relocation of waste piles, coverage of solid waste, and treatment of radioactive water and even replacement of water supplies in contaminated areas with noncontaminated water brought from elsewhere.…”
Section: Mining Sectors and Metals In The Societymentioning
confidence: 99%